Resgate da otimalidade de estratégias de alocação dinâmica com seguro e alavancagem em cenários realistas - Varanda, José Henrique de Oliveira (2018)
This study evaluates which modifications can restore the theoretical performance of dynamic asset allocation strategies that uses insurance and leverage, specifically those known as Constant Proportion Portfolio Insurance (CPPI), when confronted with realistic premises and scenarios. Simulations using GARCH models are applied to assess the effects of path dependency and volatility on those strategies and to evaluate how selected modifications mitigates those effects. These modifications are tested using the Farinelli- Tibilleti ratio and derivations, like de Upside Potential Ratio. As main finding, the modifications that mitigates path dependency can restore the theoretical performance of portfolio insurance with high significance, making those preferred strategies in relation to Buy-and-Hold (BH) or Constant-Mix (CM) for most investors in several scenarios. This work also presents a novel modification, adapted for the risk-free market in Brazil, that resulted in the best performing portfolio insurance strategy with great significance.